2018
DOI: 10.1111/eth.12769
|View full text |Cite
|
Sign up to set email alerts
|

Rational mate choice decisions vary with female age and multidimensional male signals in swordtails

Abstract: Biologists have long been interested in intransitive preferences: circular preferences in which options cannot be ranked and no single option dominates, similar to a game of rock‐paper‐scissors. Intransitive preferences violate rational decision‐making, an assumption made by models of evolution by mate choice. Despite its potential importance in the study of sexual selection, few studies have tested for intransitive preferences. Even fewer have asked whether females differ in whether they choose mates transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Female choice based only on variation in body size was intransitive, and older females were more likely to be irrational than younger ones. However, all the females exhibited transitivity when their choice was based on courtship intensity or courtship intensity plus body size ( 86 ). Studies of crickets also showed that violation of transitivity was dependent on which acoustic cues were being evaluated ( 87 ).…”
Section: Cognition and Thinking About Mate Choicementioning
confidence: 99%
“…Female choice based only on variation in body size was intransitive, and older females were more likely to be irrational than younger ones. However, all the females exhibited transitivity when their choice was based on courtship intensity or courtship intensity plus body size ( 86 ). Studies of crickets also showed that violation of transitivity was dependent on which acoustic cues were being evaluated ( 87 ).…”
Section: Cognition and Thinking About Mate Choicementioning
confidence: 99%
“…Age-dependent decision-making processes have been documented among female poeciliids. For instance, relative to smaller females, larger and presumably older female El Abra swordtails show stronger preference for courting phenotypes over coercive phenotypes [46] and exhibit less transitivity in mate choice decisions involving male size [47]. Whether the increased exposure to male harassment over a female’s lifetime contributes to the development of fast-explorative female cognitive style can only be determined with manipulative social experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral significance of stimuli is often context dependent, especially for communication signals. For example, responses to sexual signals may vary under different social, ecological, and physiological conditions ( Gall and Wilczynski 2015 ; Lea and Ryan 2015 ; Reding and Cummings 2017 , 2018 ), and in some contexts elicit no response at all ( Rand et al 1997 ). How might these different behavioral decisions result from the same stimuli?…”
Section: Introductionmentioning
confidence: 99%